Landscape character-based research of built-in areas - execution of the European Landscape Convention - Illyés, Zsuzsannaz; Báthoryné Nagy, Ildikó Réka; Varga, Dalma; Földi, Zsófia; Nádasy, László (4D Journal of Landscape Architecture and Garden Art, 2019)
The Faculty of Landscape Architecture and Urbanism has been participating in the elements of the KEHOP-4.3.0- VEKOP-15-2016-00001 strategic assessments focusing on landscape character development and green infrastructure development, aiming to provide a basis for the national implementation of the EU Biodiversity Strategy 2020 objectives and the long-term conservation and development of natural sites of community interest. The objective of this research, in connection with the project for identification of national-level landscape character types, is to map patterns created by urban spaces. On the other hand, analysis of green networks dividing, bordering and connecting built-in areas with green surfaces beyond the city limits forms a part of green infrastructure research. In this paper, we summarize the results to date on urban analyses, the common topic of the two research projects, in the context of designated built-in areas.